Dynamic simulation of plastic components - Chong, W. W. F. (Cranfield University, 2008)
The aim of the study was to simulate the dynamic properties of automotive plastic materials for an FE analysis based on the Empirical Method. The study researched into the effects of strain rate and temperature on the stress-strain behavior of the material. The studied plastic material was DYLARK 480P16 produced by NOVA Chemicals. The stress-strain behavior of plastic materials used in the automotive industry was reviewed. The study included a review of the Eyring equation used to correlate the strain rate and temperature effects of the plastic materials. Lastly, the impact properties of plastic materials were briefly discussed in the study. Material models commonly used in the industry to represent plastic materials in LS-DYNA were reviewed. The overviews on Material 24 and Material 187 were presented in this study. The theory and parameters related to the development of these material models were briefly discussed. An overview on the physical tests for the study was included. The physical tests included UNIAXIAL Tensile and Drop Weight Impact tests. Drop Weight Impact test results were provided by Jaguar Cars Limited (JCL) for DYLARK 480P16. The Drop Weight Impact tests were conducted for test temperatures at ambient temperature 85oC and -40oC,. Finite element (FE) models simulating UNIAXIAL Tensile and Drop Weight Impact tests were produced in LS-DYNA. Material 24 was used to simulate DYLARK 480P16. The stress-strain related parameters for the material model were provided by JCL. The parameter of interest for the material model was the effect of Failure Plastic Strain (FPS) value. For Drop Weight Impact tests at temperatures -40oC and 85oC, the stressstrain parameters used for the ambient temperature simulation were scaled based on the Eyring equation and an additional correction factor. All simulation results for the Drop Weight Impact tests showed correlation to physical test results provided by JCL.
Keywords: LS-DYNA; Plastic Material; Strain Rate; Temperature; Material Modelling; Eyring Equation